Water significantly changes the ring-cleavage process during aqueous photooxidation of toluene - Dong, P; Chen, Z. M.; X. Qin; Y.W. Gong (Environmental Science & Technology, 2021)
As a major constituent of aromatic compounds, toluene exists widely in environmental aqueous phases. This research investigated the aqueous-phase OH oxidation of toluene to determine how liquid water changes the radical chemistry of ring-cleavage pathways. Results show that ring-cleavage pathways through the C7 bicyclic peroxy radical (BPR) account for about 70% of total aqueous-phase oxidation pathways, which is similar to that in the gas-phase oxidation. However, detailed ring-cleavage pathways in the aqueous phase change significantly compared with those in the gas phase as shown by the decreased production of glyoxal and methylglyoxal and the enhanced production of formic acid and acetic acid as primary products, which can be attributed to the presence of liquid water. Water facilitates the formation of the BPR whose structure is different from that in the gas-phase oxidation and results in different ring-cleavage pathways through hydrogen-shift reactions. Furthermore, water helps the hydration of acyl radicals formed by the BPR to produce organic acids. With the suggested ring-cleavage mechanisms, a box model can simulate aqueous-phase product distributions better than that with the classical ring-cleavage mechanisms. Given the influence of water on reaction mechanisms, aqueous-phase oxidation of hydrophobic organic compounds may be more important than previously assumed.